2006
DOI: 10.1080/13606710500520197
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor recreation interests and environmental attitudes in Norway

Abstract: In a survey among a representative sample of the Norwegian population (N 5 2449), the associations between environmental attitudes and interest in 15 outdoor recreation activities were assessed. Environmental attitudes were measured by a short version of the New Ecological Paradigm (NEP) scale. Results suggest that most Norwegians agree with the environmental values tapped by the NEP scale. NEP scores were higher among women than among men and they were negatively associated with age. Rural inhabitants express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 25 publications
(27 reference statements)
0
31
0
5
Order By: Relevance
“…In contrast, Zelezny and Schultz (2000) claimed that women were more engaged to responsible environmental behavior than men, and Johnson, Bowker and Cordell (2004) reported that women scored higher on the New Environmental Paradigm, a scale assessing environmental beliefs, than men. In contrast, results from a Norwegian sample showed that men had higher NEP scores than women (Bjerke, et al, 2006).…”
Section: Responsible Environmental Behavior and Socio-demographic Chamentioning
confidence: 39%
See 1 more Smart Citation
“…In contrast, Zelezny and Schultz (2000) claimed that women were more engaged to responsible environmental behavior than men, and Johnson, Bowker and Cordell (2004) reported that women scored higher on the New Environmental Paradigm, a scale assessing environmental beliefs, than men. In contrast, results from a Norwegian sample showed that men had higher NEP scores than women (Bjerke, et al, 2006).…”
Section: Responsible Environmental Behavior and Socio-demographic Chamentioning
confidence: 39%
“…Furthermore, they reported that participants in motor-boating, snowmobiling and off-road driving viewed the environmental in terms of its potential use for the above vehicles. Teisl and O'Brien (2003) Recently, Bjerke Thrane and Kleiven (2006) showed that appreciative and consumptive activities did not constitute homogeneous categories that related to environmental attitudes in opposing ways. For example, various types of hunting and various types of fishing showed different associations with environmental attitudes.…”
Section: Environmental Behavior and Outdoor Recreation Participationmentioning
confidence: 99%
“…Studies incorporating general beliefs (i.e., beliefs focused on human-environment relationships in general; Best & Mayerl, 2013) often base belief constructs on the new ecological paradigm scale, adapted from the new environmental paradigm (NEP; Dunlap & Van Liere, 1978;Dunlap, Van Liere, Mertig, & Jones, 2000). Use of this environmental concern scale has resulted in wide variation in scale scores across cultural and recreational groups, and both strong and weak relationships among scale items, attitudes, and behaviors (e.g., Dunlap et al, 2000;Bjerke, Thrane, & Kleiven, 2006;Thapa, 2010).…”
Section: The Theoretical Frameworkmentioning
confidence: 98%
“…It has been argued that choice of and participation in different recreation activities are influenced by individuals' environmental values or attitudes (Bjerke et al 2006;Jackson 1986). People participating in different types of outdoor recreation may have different value orientations toward or concerning environmental conservation (Peterson et al 2008;Theodori et al 1998).…”
Section: Outdoor Recreation Participation and Environmental Behaviorsmentioning
confidence: 99%